2018
DOI: 10.1111/ajt.14929
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of using kidneys from hepatitis C nucleic acid test–positive donors for transplantation in hepatitis C–negative recipients

Abstract: Kidneys from deceased donors who are hepatitis C virus (HCV) nucleic acid test positive are infrequently used for transplantation in HCV-negative patients due to concerns about disease transmission. With the development of direct-acting antivirals (DAAs) for HCV, there is now potential to use these kidneys in HCV-negative candidates. However, the high cost of DAAs poses a challenge to adoption of this strategy. We created a Markov model to examine the cost-effectiveness of using deceased donors infected with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 24 publications
3
68
0
4
Order By: Relevance
“…A recent analysis showed that transplanting viremic donor kidneys into negative recipients could be cost‐effective with an incremental cost‐effectiveness ratio of $56 018 per quality‐adjusted life‐year (QALY) from the payer's perspective, and $4647 per QALY from the societal perspective, compared to remaining on the waitlist for one additional year . Also, Gupta et al found that kidney transplants using HCV + donors for HCV‐ recipients was a less costly approach ($138 000 versus $329 000) and resulted in slightly more years of life (YOL) (4.7 versus 4.8) when compared to HCV‐ donors for HCV‐ recipients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis showed that transplanting viremic donor kidneys into negative recipients could be cost‐effective with an incremental cost‐effectiveness ratio of $56 018 per quality‐adjusted life‐year (QALY) from the payer's perspective, and $4647 per QALY from the societal perspective, compared to remaining on the waitlist for one additional year . Also, Gupta et al found that kidney transplants using HCV + donors for HCV‐ recipients was a less costly approach ($138 000 versus $329 000) and resulted in slightly more years of life (YOL) (4.7 versus 4.8) when compared to HCV‐ donors for HCV‐ recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol identified that noninfectious donors are not susceptible to the transmission of infection, thereby avoiding expensive treatment in most of the recipients. Recently, a Markov model was used to demonstrate that the use of kidneys from deceased donors with HCV infection is likely to lead to improved clinical outcomes at a reduced cost for HCV‐negative transplant candidates . The estimation of this effect with our reduced sample size is out of the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the donor and the concept of utility, or the delivery of the most benefit to the largest number of individuals, must be examined. Two 2018 cost‐effectiveness studies showed better outcomes and less costs with HCV D + /R − kidney transplantation compared with remaining on dialysis and waiting for a HCV − kidney graft . Similarly, a 2019 cost‐effectiveness study concluded that accepting either a HCV + or HCV − liver is cost‐effective beginning at a Model for End‐Stage Liver Disease (MELD) score of 22, as well as at any MELD score if a patient has a reduced quality of life compared with accepting only HCV − livers .…”
Section: Utilitymentioning
confidence: 99%
“…Two 2018 cost-effectiveness studies showed better outcomes and less costs with HCV D + /R − kidney transplantation compared with remaining on dialysis and waiting for a HCV − kidney graft. 22,23 Similarly, a 2019 cost-effectiveness study concluded that accepting either a HCV + or HCV − liver is cost-effective beginning at a Model for End-Stage Liver Disease (MELD) score of 22, as well as at any MELD score if a patient has a reduced quality of life compared with accepting only HCV − livers. 24 Another modeling study published in 2018 demonstrated that for patients with MELD scores ≥20, accepting either a HCV + or HCV − liver versus only HCV − livers led to an increase in life expectancy, indicating that HCV D + /R − LT may improve wait-list survival.…”
Section: Utilitymentioning
confidence: 99%